Clinical and Endoscopic Features in Helicobacter Pylori Infection: Literature Review - Ghina Tsuraya Salsabila Budiman; Muhammad Begawan Bestari; Sri Suryanti (The Indonesian Society for Digestive Endoscopy, 2021)
Helicobacter pylori is a common infection worldwide and can cause functional dyspepsia, gastritis, and peptic ulcers, leading to gastric cancer. The very diverse clinical outcomes and symptoms of this infection are difficult to distinguish from one another. Endoscopy is one of the methods used to detect Helicobacter pylori infection. Still, it has various endoscopic features, has the possibility of false-negative results, and requires skill to get the maximum results.This study found that infection can cause various clinical manifestations due to different virulence factors of Helicobacter pylori bacteria. In functional dyspepsia, the patient's most common symptoms are epigastric pain, nausea, and vomiting. In gastritis, Helicobacter pylori infection often causes chronic gastritis with topographic features of pangastritis, and endoscopic features that are usually found are redness, swelling, and regular arrangement of collecting venules (RAC). The most common symptom in peptic ulcers is pain that occurs after eating or at night, and this infection can cause duodenal and gastric ulcers. Currently, the relationship between Helicobacter pylori infection and gastroesophageal reflux disease (GERD) is controversial. In gastric cancer, the most common symptoms are weight loss and repeated vomiting. This infection is more likely to causes intestinal-type gastric cancer.